Design and implementation of a single-phase to three-phase space-vector pwm-based matrix converter system for induction motor drives - Velu, Vengadeshwaran (2016)
The advancement in the power electronics devices and modules creates an avenue to design and develop innovative direct ac-ac converters with more efficient and effective characteristics. Poly phase devices such as three phase induction motors have many advantages compared to its single phase counter parts in terms of performance efficiency and load characteristics. In real life, three phase power supply is not readily available in many places, especially in the remote locations, rural areas, hill stations, ordinary homes etc. Thus, having a converter that’s capable of converting the available single phase source to a three phase power supply will be very useful in such environments. Matrix Converter is an emerging power electronics technology based direct ac-ac converter that replaces the existing multi-stage and energy storage element conversion topologies. Compared to the other available ac-ac converters, Matrix converter has many advantages such as bidirectional energy flow capability, less harmonics and high power factor operation. Matrix Converter arrays are made of IGBT based bidirectional switches with reverse blocking capabilities. Similar research initiatives reported that the switching sequences of the bidirectional switches are controlled by different modulation algorithms such as pulse width modulation technique, sinusoidal pulse width modulation technique etc. However, the output voltages of these topologies suffer from low voltage transfer ratio and high harmonic content. The objective of this research is to design and develop a single phase to three phase direct ac-ac Bidirectional switches based Matrix Converter system for operating the poly phase loads using a single phase source. A novel approach is adopted by employing the Space Vector Pulse Width modulation algorithm to produce the switching sequences of the bidirectional switches of the single-phase to three-phase Matrix Converter. A novel technique of employing a sinusoidal signal as reference is used in order to phase shift the space vector pwm pulses during negative cycle operations. A novel segregation technique is adopted in order to segregate the input signal into six sectors voltages to distribute equally among the output phases. A unique finding to achieve the balanced output voltages with relatively high voltage transfer ratio is presented. The proposed topology was modelled in the Matlab/Simulink environment and tested for functional efficacy. The hardware of the Matrix Converter system is implemented using six IGBT based bidirectional switches in a (2 x 3) array. Digital Signal Processor is used as a control system to produce the switching sequences of the individual bidirectional switches based on space vector Pulse Width Modulation algorithm. Six sets of IGBT core drivers are used to provide the necessary switching pulses to gate terminals of the individual bidirectional switches based on the digital signal processor outputs. The hardware circuit was tested under different power factor loads such as unity, lagging and leading power factor loads and under different frequency operations. The characteristics of the proposed system were studied under variable reference frequencies operations. The experimentation results showed that the proposed system achieved high voltage transfer ratio compared to other similar research initiatives. Furthermore, based on the variation of reference frequency characteristics it has been observed that when the reference frequency is adjusted beyond 150 Hz, the output voltages are found to be converging and becoming more balanced. Under low reference frequency operation, the output voltages are not balanced due to the low number of segregations of input signal that made the converter operating under high segregation angle. However above 150 Hz of reference frequency operation, the output voltages are found to be balanced due to the considerable reduction in the segregation angle. Under the balanced condition, the matrix converter produces an output line to line voltage of 80.8% of the available input voltage. Under this condition, a voltage transfer ratio of 0.466 is achieved. These unique findings provide more opportunity for further expansion of research to attain a higher voltage ratio with balanced voltages and less percentage total harmonic distortion. The project attained all its objectives with unique findings.